Extractive revenues and government spending: Short- versus long-term considerations - Frederick van der Ploeg; Anthony J. Venables (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The prescription of optimally managing natural resource revenue windfalls by smoothing consumption across generations using an intergenerational sovereign wealth fund that only invests in foreign assets is not appropriate for resource-rich developing economies. It is better for these economies to use their windfalls to boost investment in the domestic economy, especially when they confront capital scarcity and have poor access to international capital markets. However, it is important for such economies to have a parking fund to temporarily 'park' funds until absorption constraints are alleviated, and a stabilization fund to smooth out volatile budgets given the high stochastic volatility of commodity prices, especially if the economy is inflexible and has few other ways of adjusting to shocks.
Keywords: E60; F43; H21; H63; O11; Q33; 330; resource curse; managing windfalls; fiscal rules